A sol–gel route to titanium nitride conductive coatings on battery materials and performance of TiN-coated LiFePO4. Issue 5 (13th January 2017) - Zhang, Min; Garcia-Araez, Nuria; Hector, Andrew L.; Owen, John R.
Abstract : New approaches to produce nanocrystalline TiN materials with high conductivity and their application as conductive coatings on battery materials have been developed. These were found to be effective at delivering a good performance with LiFePO4 . Abstract : New approaches to produce nanocrystalline TiN materials with high conductivity and their application as conductive coatings on battery materials have been developed. Sol–gel synthesis routes using tetrakis(dimethylamido)titanium(iv ) and a propylamine or ammonia cross linking agent, followed by thermal treatment under NH3 or H2 + N2, were found to produce TiN powders of small crystallite size (<10 nm), with good conductivity in selected cases. The most promising synthesis conditions were used to produce even TiN coatings on LiFePO4 particles, and the resulting materials exhibited significantly improved electrochemical performance relative to uncoated LiFePO4, in terms of higher specific capacity, cycle stability and rate capability. The material with the optimum 10 wt% TiN content exhibited a discharge capacity of 159 mA h g −1, that is ∼93% of the theoretical capacity, when charge/discharge rates of 0.1C were applied. The results demonstrate the suitability of this new route to produce TiN coatings, which could also be applied to high voltage materials or for materials to be operated at high temperatures, where corrosion or degradation of other coating materials ( e.g. carbon) would be problematic.